Ultrafast X‐ray imaging of laser–metal additive manufacturing processes. (14th August 2018) - Parab, Niranjan D.; Zhao, Cang; Cunningham, Ross; Escano, Luis I.; Fezzaa, Kamel; Everhart, Wes; Rollett, Anthony D.; Chen, Lianyi; Sun, Tao
Abstract : The high‐speed synchrotron X‐ray imaging technique was synchronized with a custom‐built laser‐melting setup to capture the dynamics of laser powder‐bed fusion processes in situ . Various significant phenomena, including vapor‐depression and melt‐pool dynamics and powder‐spatter ejection, were captured with high spatial and temporal resolution. Abstract : The high‐speed synchrotron X‐ray imaging technique was synchronized with a custom‐built laser‐melting setup to capture the dynamics of laser powder‐bed fusion processes in situ . Various significant phenomena, including vapor‐depression and melt‐pool dynamics and powder‐spatter ejection, were captured with high spatial and temporal resolution. Imaging frame rates of up to 10 MHz were used to capture the rapid changes in these highly dynamic phenomena. At the same time, relatively slow frame rates were employed to capture large‐scale changes during the process. This experimental platform will be vital in the further understanding of laser additive manufacturing processes and will be particularly helpful in guiding efforts to reduce or eliminate microstructural defects in additively manufactured parts.